2023
DOI: 10.3390/s23084132
|View full text |Cite
|
Sign up to set email alerts
|

Array of Miniaturized Amperometric Gas Sensors Using Atomic Gold Decorated Pt/PANI Electrodes in Room Temperature Ionic Liquid Films

Abstract: Miniaturized sensors possess many advantages, such as rapid response, easy chip integration, a possible lower concentration of target compound detection, etc. However, a major issue reported is a low signal response. In this study, a catalyst, the atomic gold clusters of Aun where n = 2, was decorated at a platinum/polyaniline (Pt/PANI) working electrode to enhance the sensitivity of butanol isomers gas measurement. Isomer quantification is challenging because this compound has the same chemical formula and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 51 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…When the sensor was exposed to NH 3 , NH 3 captures H + from the -NH- groups, leading to a reduction in the polaron density along the main chain of polyaniline, rendering the PANI in a highly resistive state. The opposite process would occur when the sensor was placed back in air [ 16 ]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the sensor was exposed to NH 3 , NH 3 captures H + from the -NH- groups, leading to a reduction in the polaron density along the main chain of polyaniline, rendering the PANI in a highly resistive state. The opposite process would occur when the sensor was placed back in air [ 16 ]. …”
Section: Resultsmentioning
confidence: 99%
“…PANI-sensor-enhanced NH 3 -sensing performance primarily involves strategies such as the formation of p-n heterojunctions by combining PANI with an n-type metal oxide semiconductor (MOS) [ 12 , 13 ], the construction of hollow structures [ 14 , 15 ] and hierarchical structure gas-sensitive materials [ 16 , 17 ]. That is to say, the modulation of surface morphology is particularly essential to enhance the gas-sensitive performance of PANI, which mainly concerns the property enhancement brought by a large specific surface area, multiple active sites and a high porosity with microstructural advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, it is widely reported that RTIL has a wider EC potential window than liquid electrolytes which allows for detecting more target gasses where the redox reaction takes place at a high EC potential. Lastly, using RTIL, a thin film for a miniaturized AGS can be realized and the fluidity issue can be removed due to its high viscosity [27]. In this section, we also provide brief information regarding the structure and several physical-chemical properties of RTIL.…”
Section: Agss With Room Temperature Ionic Liquids (Rtils)mentioning
confidence: 99%
“…However, a low sensor signal is the main issue; hence, the atomic catalyst is indeed required to enhance the sensitivity. In the miniaturized AGS, Room Temperature Ionic Liquid (RTIL) was used as a substitute for the aqueous electrolyte due to fluidity and evaporation issues [27]. Although there are many works related to RTILs used for miniaturized AGSs [28,29], using atomic gold with the RTIL is still very new and can be explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation